Motives for acquiring and saving and their relationship with object attachment. (June 2021) - David, Jonathan; Blonner, Marika; Forbes, Miriam K; Norberg, Melissa M
Highlights: In this paper we review object attachment and the motives to acquire and save. The links between object attachment and motives to acquire and save are dynamic. We present a theoretical framework to guide future research in this area. Further experimental and longitudinal studies can elucidate these dynamic links. Abstract : Motives for acquiring and saving objects are closely linked to object attachment, but the nature of these associations has not been established. A better understanding of the motives for acquiring and saving possessions and how they relate to object attachment may reveal insights into the underpinnings of hoarding disorder. In turn, these insights can aid in identifying optimal targets for interventions for hoarding problems. In this paper, we propose a simple theoretical model of the dynamic associations among motives to acquire objects, object attachment, and motives to save objects, grounded in a review of the extant literature. Our hope is that this model provides a useful framework to structure future research.